1972
DOI: 10.1111/j.1478-4408.1972.tb03098.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation and Administration of Research

Abstract: The objective of this paper is to explain how a system for the evaluation and administration of research and development can be set up in an organisation. It presents a practical approach to the problem of selecting the best research programme and then controlling it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It must make a significant contribution to the future well‐being of the industry or organisation and not be an embarrassment to the organisation’s resources. Furthermore, the project leader’s involvement should not be concluded until the benefits of the research have been fully exploited [24]. The major objective for the introduction of new technology, and therefore for R&D, was often seen as being to reduce unit production cost and thereby to increase profitability.…”
Section: Managing Randdmentioning
confidence: 99%
“…It must make a significant contribution to the future well‐being of the industry or organisation and not be an embarrassment to the organisation’s resources. Furthermore, the project leader’s involvement should not be concluded until the benefits of the research have been fully exploited [24]. The major objective for the introduction of new technology, and therefore for R&D, was often seen as being to reduce unit production cost and thereby to increase profitability.…”
Section: Managing Randdmentioning
confidence: 99%
“…Research and development in the textile industry is essential for its continuing success, even with a mature industry and in times of recession [21]. A practical approach was given for selecting and controlling the best research programme [22], which indicated that projects relevant to the practical operation of the industry were difficult to find. Management of all the aspects of textile research was extensively reviewed [23].…”
Section: Wet Processing Researchmentioning
confidence: 99%